Analysis of Socioeconomic and Ecological Factors Affecting Willingness to Pay in the Glintung Go Green Environmental Conservation Initiative - Muljaningsih, Sri; Ekawaty, Marlina; Anggraini, Ika Khusnia; Galuh, Ajeng Kartika (AIBPM Publisher, 2024)
This study examines the impact of socioeconomic and ecological factors on the Willingness to Pay (WTP) for environmental conservation within the Glintung Go Green initiative. The research analyzes key variables, including income , education , employment status , age ), gender , length of residency , flood frequency , and flood impact , to understand their influence on WTP. Using Smart-PLS, the results show that income, education, and employment status positively affect social and ecological factors, which in turn significantly influence WTP (coefficient = 0.533). However, age and length of residency display a negative relationship, suggesting that younger and more recent residents may be more willing to contribute to conservation efforts. This study highlights the importance of socioeconomic improvements to enhance community readiness for supporting environmental initiatives. The findings provide valuable insights for policymakers aiming to promote sustainable practices in urban communities, particularly by leveraging socioeconomic and ecological factors that motivate financial contributions to conservation projects like Glintung Go Green.Keywords: